Cognition, affect, and learning aspirations in public health development history education: cross-sectional associations in a large sample of university students in Eastern China - Shiyu Zhang (Frontiers in Public Health, 2026)
Introduction Historically grounded narratives are increasingly incorporated into values-oriented higher education, yet limited empirical research has examined how university students’ appraisals of public health development history are associated with their affective responses and stated learning demands. Guided by the Cognition–Affect–Conation (CAC) framework as a conceptual organizing framework, this study examined the cross-sectional associations among Educational Cognition, Educational Emotion, and Public Health Learning Aspirations (PHLA) within Ideological and Political Education (IPE) in Chinese universities. PHLA was used as an umbrella term for two related forms of stated educational demand: Demand for Educational Resources (DER) and Demand for Educational Content (DEC). Methods A cross-sectional online survey was administered in September 2025 to 1,142 university students recruited through stratified cluster sampling; 92.2% attended institutions in Eastern China. From a self-developed 33-item questionnaire, 24 substantive Likert-type items measuring Educational Cognition, Educational Emotion, DER, and DEC on five-point scales were analyzed. Descriptive statistics, Spearman rank-order correlations, and bootstrap cross-sectional indirect-association models were estimated using PROCESS Macro Model 4 for SPSS with 5,000 resamples. Results All four study variables had means above 4.0, with Educational Emotion showing the highest mean ( M = 4.528, SD = 0.589). The variables were positively intercorrelated ( ρ = 0.649–0.826, all p < 0.01), supporting H1. In the specified cross-sectional regression models, Educational Cognition was positively associated with Educational Emotion ( β = 0.65), DER ( β = 0.56), and DEC ( β = 0.45; all p < 0.001), supporting H2. The indirect association involving Educational Emotion was statistically different from zero for DER (estimate = 0.20, 95% bootstrap CI [0.15, 0.23]; 26% of the total association) and DEC (estimate = 0.28, 95% bootstrap CI [0.23, 0.33]; 39% of the total association). These estimates came from separate outcome models and were not directly compared. Discussion The findings describe the co-occurrence of educational appraisal, affective-motivational response, and stated learning demand, a pattern compatible with the CAC framework but not evidence of temporal mediation or causality. By distinguishing substantive content demand from resource-related demand, the study provides a preliminary basis for examining how public health development history is appraised within value-laden education. The findings may inform the development of historical content and supporting resources in IPE and medical humanities curricula. Interpretation remains limited by self-report measurement, possible socially desirable responding, operational overlap among the study-defined constructs, and the concentration of the sample in Eastern China.